Efforts To Preserve Local Wisdom In The Hape Nulif Tradition In Duawutun Village, Nagawutung District, Lembata District - St. Sara N.K. Ladopurap; Darman Manda (Gudang Jurnal Multidisiplin Ilmu, 2026)
The research findings indicate that community participation from Duawutun and Wuakerong villages in the Hape Nulif tradition extends beyond mere physical presence, manifesting as structured and active involvement throughout every stage of the ritual. The community demonstrates a high spirit of gotong royong (mutual cooperation), reflected in the clear distribution of roles among traditional leaders, youth figures, and women. This collective cooperation encompasses everything from ritual logistical preparations to the execution of core processions, which directly strengthens social cohesion and solidarity among residents. Substantially, this tradition serves as a space for articulating local cultural identity, bridging material and spiritual dimensions where reverence for ancestors and nature remains a central value. The intergenerational distribution of responsibilities ensures that every community member feels a profound sense of belonging toward the preservation of this local wisdom. Consequently, the Hape Nulif ritual becomes a crucial instrument in bolstering cultural resilience amidst modernization, while reaffirming the position of the Duawutun community as one that steadfastly upholds noble human values and togetherness within a sacred traditional framework.